ANALISIS BUTIR SOAL PILIHAN GANDA MATEMATIKA SEKOLAH MENENGAH PERTAMA - Hodiyanto, Hodiyanto (Universitas PGRI Adi Buana Surabaya, 2017)
The Good instruments have good realibility and each items have good discrimination power. But the facts, most teachers in making tests just take from a book. Therefore, the author feel the need to analyze the items that are used as an instrument by teachers, so that the results of research can provide input to the instrument used. The purpose of this research is to discribe the instrument viewed from the reability, the items viewed from discrimination power, and test distractors. This research method used is descriptive method. Based on the results of the analysis are obtained that the instrument realibility isn’t good, the items have ugly discrimination power, and the distractors are not function. Keywords: evaluation of learning, realibility, discrimination power